2017
DOI: 10.4300/jgme-d-16-00372.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Interventions to Reduce Resident Physician Burnout: A Systematic Review

Abstract: Background Studies report high burnout prevalence among resident physicians, with little consensus on methods to effectively reduce it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
214
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(244 citation statements)
references
References 29 publications
4
214
1
8
Order By: Relevance
“…Burnout is a syndrome of emotional exhaustion (feeling overwhelmed by job demands and depletion of emotional resources), depersonalization (feelings of cynicism and detachment toward patients), and decreased perceived personal accomplishment (decrease in feelings of work competence and achievement) [2,3]. It develops in response to long-term emotional and interpersonal occupational stressors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout is a syndrome of emotional exhaustion (feeling overwhelmed by job demands and depletion of emotional resources), depersonalization (feelings of cynicism and detachment toward patients), and decreased perceived personal accomplishment (decrease in feelings of work competence and achievement) [2,3]. It develops in response to long-term emotional and interpersonal occupational stressors [3].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Apart from the implementation of the 80-hour work week, educators have made little progress in combating resident burnout. 5 One potential contributing factor that has received less attention is the learning environment itself. 4 A meta-analysis from JAMA Surgery that looked at resident attrition showed that women are more likely to leave surgical residency than men are, which suggests that there may indeed be sex-related differences in the training experience.…”
mentioning
confidence: 99%
“…W e read the review of burnout interventions by Busireddy and colleagues 1 with interest and applaud the authors' efforts to synthesize evidence around interventions to reduce burnout among trainees. We published a study that examined the impact of a formal narrative medicine curriculum among obstetrics and gynecology residents at 3 training programs, which demonstrated a significant improvement in emotional exhaustion (measured by the Maslach Burnout Inventory) for residents who attended more of the reflective writing workshops, with a moderate effect size as measured by Cohen's d. While the authors 1 did not indicate in their methods when they performed their query of the literature, the review includes studies from 1991 to 2015, 1 year before our study was in print.…”
mentioning
confidence: 99%
“…We would agree with Busireddy and colleagues' conclusion that adding required activities in the name of improving wellness may miss the mark with residents who are already chronically overburdened. 1 For this reason, our curriculum takes place during protected time and does not include any preparatory reading or other homework. It will be challenging to explore whether this and other interventions aimed at improving the learning environment for residents are effective across sites and specialties.…”
mentioning
confidence: 99%